Atividade salineira em manguezais do semiárido: impactos ambientais e reflexos econômicos da recuperação ou compensação ambiental das áreas degradadas - Fernandes, Rogério Taygra Vasconcelos (Universidade Federal Rural do Semi-Árido, 2019)
The Brazilian White Coast region, or solar saltworks zone, is today an area of typical conflict situation involving an important economic sector, salt production and one of the most productive coastal ecosystems, mangroves. In this context, studies that can evaluate the real environmental impacts involved in salt production in mangrove areas, as well as the economic impacts of the recovery of these degraded areas or of environmental compensation through their use, become an important tool for researchers, entrepreneurs, environmental regulatory organizations. Thus, the objective was to evaluate the environmental impacts of the saline activity in mangroves, as well as the impacts and economic consequences of the recovery or environmental offsets of the degraded areas. The studies were carried out in the saltworks area of the estuary of Rio das Conchas, RN, where the two main stages of a saltworks enterprise were analyzed: installation and operation, and in the Apodi/Mossoró estuary, through of the land use class mapping in the Permanent Preservation Areas (PPAs) of this estuary, where the economic impact was determined by assigning values for each type of land use through the creation of 4 scenarios. From then on, the Opportunity Cost (OC) was determined for each scenario, being considered the most advantageous model that obtained the lowest value. In a complementary study, 27 salinas installed in the Brazilian White Coast region were evaluated for the occupation of PPAs, and estimated the Environmental Offsets (EO) and Economic Impact (EI) values of vacant areas. It was possible to verify the occupation and degradation of mangrove areas in the area where saltworks is currently installed in the Conchas River, which had an area of 1,151.57 hectares deforested with mangrove vegetation, while during the operational phase, the average salinity remained above of 30,00‰, characterizing the environment as saline, which is acceptable for this estuary. The lands of the PPAs were occupied mainly by the solar saltworks (varying between 10 and 43%), while the estimate of recovery of all this occupied area would have a negative impact on the local and national economy. On the other hand, the total EO estimated was US$ 1,530,227.32, while IE resulting from the vacancy of the PPA by the saltworks was estimated at US$ 3,258.88/ha, and a total combined revenue loss of US$ 96,744,624.45 For all the evaluated enterprises the value corresponding to EO was lower than the Economic Impact resulting from the vacancy of the PPA. In view of the obtained results, it is evident that the recovery or compensation of the degraded areas and the control of the effluent discharge rate, associated to the search for treatment or reuse techniques, should be encouraged. Such measures would enable the development of salt activity in a sustainable way, since the salt production has great relevance in the local and national socioeconomic aspect
Keywords: Áreas de Preservação Permanente; Ecossistema; Estuário; Sal; Salinas; Ecosystem; Estuary; Permanent Preservation Areas; Salt; Solar Saltworks; CIENCIAS AGRARIAS::MEDICINA VETERINARIA